CD8+ Th17 Mediate Costimulation Blockade Resistant Allograft Rejection in T-bet Deficient Mice - Burrell, Bryna E. (2008)
While studying T helper (Th) responses induced by cardiac transplantation, we observed that mice deficient in the Th1 transcription factor T-bet (T-bet-/-) mount both Th1 and Th17 responses, while wild type (WT) recipients mount only Th1 responses. Cells producing both IFNγ and IL-17 were readily detectable within the rejecting graft of T-bet-/- recipients, but were absent from the spleen indicating that the in vivo microenvironment influences Th function. In addition, disrupting CD40 – CD40 ligand (CD40L) costimulatory interactions was highly effective at prolonging allograft survival in WT mice, but ineffective in T-bet-/- recipients. Herein, we report that CD8+ Th17 mediate costimulation blockade resistant rejection in T-bet-/- allograft recipients. Depleting CD8+ cells or neutralizing IL-17 or the Th17-inducing cytokine IL-6 ablated the Th17 response and reversed costimulation blockade resistant graft rejection. Neutralizing IL-4 in IFNγ-/- allograft recipients did not induce Th17, suggesting that T-bet, rather than IL-4 and IFNγ (known inhibitors of Th17), plays a critical role in negatively regulating Th17 in the transplant setting.